Problematika diverzity v sociální práci - Pastrňák, René (Univerzita Pardubice, 2009)
Multicultural communication is one of the basic social skills of any person who, during his/her work, study, travel meets or cooperates with the members of different cultures. It represents the ability to understand the existing cultural dimension and to manage them appropriately in the context of his/her social role and sub-task, work, study or future knowledge.
Keywords: migration; culture; social assistance/help; diversity; communication skills